2021
DOI: 10.1038/s41467-021-21963-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling PRMT methylome reveals roles of hnRNPA1 arginine methylation in RNA splicing and cell growth

Abstract: Numerous substrates have been identified for Type I and II arginine methyltransferases (PRMTs). However, the full substrate spectrum of the only type III PRMT, PRMT7, and its connection to type I and II PRMT substrates remains unknown. Here, we use mass spectrometry to reveal features of PRMT7-regulated methylation. We find that PRMT7 predominantly methylates a glycine and arginine motif; multiple PRMT7-regulated arginine methylation sites are close to phosphorylations sites; methylation sites and proximal seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 86 publications
10
102
0
Order By: Relevance
“…Unlike many of the other epigenetic inhibitors that induce ERV expression, MS023 treatment triggers dsRNA accumulation from intron retained RNAs. While PRMT enzymes are often classified as epigenetic targets based on their histone substrates, PRMTs have a much broader set of targets, especially RNA-binding proteins involved in mRNA splicing 39,40 . Given these broad roles of type I PRMT on RNA splicing, our discovery is consistent with the recent report showing that spliceosome-targeted therapies result in intron-containing transcripts that form double-stranded RNAs 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike many of the other epigenetic inhibitors that induce ERV expression, MS023 treatment triggers dsRNA accumulation from intron retained RNAs. While PRMT enzymes are often classified as epigenetic targets based on their histone substrates, PRMTs have a much broader set of targets, especially RNA-binding proteins involved in mRNA splicing 39,40 . Given these broad roles of type I PRMT on RNA splicing, our discovery is consistent with the recent report showing that spliceosome-targeted therapies result in intron-containing transcripts that form double-stranded RNAs 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mis-spliced mRNAs with retained introns formed double-stranded structures that accumulated in the cytoplasm 38 . Given the broad effects of type I PRMT on mRNA splicing 13,16,39,40 , we hypothesized that induction of dsRNA formation in response to MS023 treatment was due to direct deregulation of RNA splicing 41,42 . To test this hypothesis, RNA-seq data were analyzed to identify the MS023-associated disruptive alternative splicing events (ASEs).…”
Section: Type I Prmt Inhibition Induces Dsrna Accumulation From Intron-retained Rnasmentioning
confidence: 99%
“…In addition, VRK1 and HNRNP A1 are frequently overexpressed in several human cancers, including hepatocellular carcinoma (HCC) and the overexpression of VRK1 and HNRNP A1 is correlated with a poor prognosis for HCC patients [ 17 ]. Arginine methylation of the hnRNP A1 and a family of protein arginine methyltransferases (PRMTs) are found to be overexpressed in breast, prostate and colon cancer cells [ 22 ]. One study showed an increased expression level of HNRNP A1 in cervical cancer cells including HeLa, providing evidence that the expression of HNRNP A1 is closely related to HeLa cell proliferation, invasion and migration [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In light of the above discussed PRMT7 and PRMT5 crosstalk, it is possible that the observed regulation of H4R3me2s by PRMT7 was an outcome of PRMT7 activating the PRMT5 dimethyltransferase function. Another early study has reported PRMT7-mediated methylation of small nuclear ribonucleoproteins (snRNPs) [ 21 ] that was subsequently confirmed in the large-scale mass spectrometry study [ 28 ].…”
Section: Enzyme Function Of Prmt7mentioning
confidence: 99%
“…Nevertheless, three recent studies on PRMT7 dependent methylome in mammalian cell lines and Leishmania sp. parasite highlight the broad diversity of PRMT7 substrates [ 13 , 28 , 38 ]. The largest category of proteins enriched in the PRMT7 methylated hits was RNA binding and metabolism-associated proteins, a finding that was consistent in all three studies.…”
Section: Enzyme Function Of Prmt7mentioning
confidence: 99%